Modified constipation assessment scale is an effective tool to assess bowel function in patients receiving radiotherapy. - Isenring E; Bauer J; Capra S (Nutrition & Dietetics)
Objectives: To determine the reliability and relative construct validity of the Modified Constipation Assessment Scale (MCAS) and use it to assess bowel function in oncology outpatients receiving radiotherapy.Design: Validation study using data collected as part of a randomised controlled trial. Relative construct validity was investigated by triangulating the MCAS with bowel function assessed by the quality of life questionnaire, QLQ-C30, and professional field notes.Subjects: Sixty subjects (male : female 51 : 9; mean age 61.9 +/- 14 years) receiving at least 20 fractions of radiotherapy to the gastrointestinal or head and neck area.Setting: Australian private radiotherapy centre.Main outcome measure: Bowel function assessed by the MCAS.Statistical analyses: Test-retest reliability was assessed by correlation. Mann-Whitney U-scores compared differences between the groups and Fisher's exact tests investigated the proportion of subjects experiencing changes in MCAS scores.Results: The MCAS proved to be reliable with a mean difference between repeated tests in subjects being less than 1% of the maximum score. For bowel function assessed by the MCAS and the QLQ-C30, 53% of responses were ranked in the same tertile. Of a total of 60 scores, six were misclassified (one false negative by the MCAS, five false negative by the QLQ-C30). The MCAS provided more information than the QLQ-C30 alone for 27 (45%) of the bowel-function scores.Conclusion: The MCAS has acceptable reliability and relative construct validity and is useful in assessing bowel function in patients receiving radiotherapy. Further work should be conducted on the validity and reliability of the MCAS prior to its use in other populations.